Aspectos epidemiológicos do câncer em cães da região central do Rio Grande do Sul: 50 anos (1964-2013) - Flores, Mariana Martins (2016)
The goals of this study were: (1) to analyze the occurrence as a cause of death or reason for euthanasia in autopsied dogs in the Laboratório de Patologia Veterinária (LPV), Universidade Federal de Santa Maria (UFSM) over 50 years ( 1964-2013), with emphasis on epidemiological aspects; (2) to analyze the epidemiological and pathological aspects of hemangiosarcoma in dogs from LPV-UFSM; (3) to analyze the applicability of ancillary tests in the diagnosis and prognosis of cutaneous mast cell tumors in LPV-UFSM. For the first and second studies, necropsy files from LPV-UFSM were reviewed, and information about gender, age, race and cause of death were collected. This information was separated by decade (1964-2013). Later, those protocols in which the cause of death was attributed to some form of cancer were separated, and the prevalence and epidemiological aspects of cancer were analyzed per decade. For the third study, cases diagnosed as hemangiosarcoma were separated, and information about the macroscopic aspects of the tumors were collected. New histology slides were stained and the cases were submitted to immunohistochemistry for von Willebrand factor. For the fourth study, the biopsy files from LPV-UFSM were reviewed, and cases diagnosed as cutaneous mast cell tumor were separated. These cases were submitted to histological grading (KIUPEL et al. 2011), immunohistochemistry (KIT and Ki-67) and PCR for mutations in exon 11. Of the 7,780 dogs necropsied, 11.1% died or were euthanized due to cancer. The prevalence of cancer experienced a significant increase over 50 years. The most prevalent tumors were mammary carcinomas (24.5%), lymphomas (8.8%), skeletal osteosarcoma (7.8%), cholangiocarcinoma (5.5%), cutaneous mast cell tumors (5.4%) and multicentric hemangiosarcoma (3.3%). The prevalence of cancer was higher in females (58.5%) and the old-aged dogs (56.2%), but similar between the purebred (60.4%) and mixed breed dogs. The prevalence was higher in Boxer and Rottweiler. As for the 40 haemangiosarcomas analyzed, the German Shepherd was most affected. The main organs affected were spleen, lung, liver and peritoneum. Most tumors were histologically well differentiated and low grade, and all cases tested showed immunostaining for von Willebrand factor. As for mast cell tumors, 40 cases were recovered from the LPV-UFSM files, of which 69.2% were low grade and 30.8% were high grade. All had a KIT expression pattern II and 30.6% had a high growth fraction (Ki-67). Two tumors were positive for mutations. Through this work, it was possible to prove that cancer has increased as a cause of death in autopsied dogs from LPV-UFSM over the years. This study also made it possible to analyze the different epidemiological and pathological aspects of hemangiosarcomas from LPV-UFSM, and to prove the applicability of ancillary techniques in the prognosis of canine cutaneous mast cell tumors from this laboratory.